Biological Periodicity’s Atomic Mechanism Disposes of the “Current Theory” of Evolution - Lima-de-Faria, Antonio (Organisms. Journal of Biological Sciences, 2021)
Physics led the way in the creation of Molecular Biology by employing X-ray crystallography in the elucidation of the atomic structure of proteins and DNA. Now it is physics again, by using large accelerators of electrons and neutrons, that is transforming molecular biology into Atomic Biology. This transformation process is guided by the establishment of periodicity, a phenomenon that can now be shown to start with elementary particles, to extend to atoms and macromolecules, and to occur equally among living organisms including humans. Biological periodicity was established in the following properties: vision, regeneration, luminescence, flight, placenta, penis, plant carnivory and mental ability. Significant is that three of these properties do not start at the cell or the organism, as previously thought, but emerge already in crystals and minerals which have no genes, and where organization is decided by atomic and electronic interactions. The punctuated reappearance of a given property, which leads to periodicity, is based on its own evolution of DNA. This is demonstrated by the formation of the placenta, which in plants and in humans, is decided by the same DNA sequences. Also, vision, which appears in the simplest invertebrates as well as in humans results from the action of the same gene Pax6. It is this DNA homology which allows the reappearance of the same pattern, in the most different organisms. The law of periodicity which has been enunciated at the atomic level holds equally well for the periodicity found in living organisms allowing predictions.